2018
DOI: 10.4995/wrs.2018.10182
|View full text |Cite
|
Sign up to set email alerts
|

Performance, haemato-biochemical indices and antioxidant status of growing rabbits fed on diets supplemented with Mucuna pruriens leaf meal

Abstract: <p>The effects of dietary <em>Mucuna pruriens</em> leaf meal (MLM) supplementation on rabbits’ performance, haemato-biochemical indices and antioxidant status outside their thermal neutrality zone (21 to 25°C) were evaluated. One hundred and twenty 35-d old crossbreed (Chinchilla×New Zealand) rabbits weighing 694±5 g were allotted to 4 treatments (30 rabbits/treatment; 3 rabbits/replicate). A basal diet (crude protein: 16.9%, crude fibre: 17.6%, digestible energy: 2671 kcal/kg) was divided in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 38 publications
1
16
0
Order By: Relevance
“…The observed increase serum glutathione peroxidase and superoxide dismutase activities in the birds fed MSP diets further revealed the antioxidant properties of MSP and its potentials to improve the antioxidant status of the experimental birds. This result is in tandem with the report of Oloruntola et al, (2018) who reported increased antioxidant activities in rabbits fed mucuna leaf meal supplemented diets. The improved oxidative status observed in birds fed the MSP supplemented diets in this study could also be linked to the improved performance recorded in these same set of birds because oxidative stress has been reported as one of the important factors preventing tropical domestic animals from attaining their full growth potential (Jimoh, 2018).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The observed increase serum glutathione peroxidase and superoxide dismutase activities in the birds fed MSP diets further revealed the antioxidant properties of MSP and its potentials to improve the antioxidant status of the experimental birds. This result is in tandem with the report of Oloruntola et al, (2018) who reported increased antioxidant activities in rabbits fed mucuna leaf meal supplemented diets. The improved oxidative status observed in birds fed the MSP supplemented diets in this study could also be linked to the improved performance recorded in these same set of birds because oxidative stress has been reported as one of the important factors preventing tropical domestic animals from attaining their full growth potential (Jimoh, 2018).…”
Section: Discussionsupporting
confidence: 90%
“…These plants are rich in secondary plant metabolites with robust capacity to elicit antioxidant, antimicrobial, antiviral, and immune-modulatory effects in a biological system (Applegate et al, 2010). Application of phytogenics feed additives has been reported to enhanced body weight and feed efficiency (Reis et al, 2018, Flees et al, 2020, egg production (Sharma et al, 2020), improve carcass yield, gut integrity and meat quality (Reis et al, 2018;Oloruntola et al, 2018), boost reproductive performance, serum enzymatic and antioxidant activity (Reis et al, 2018;Oloruntola et al, 2019), and reduced intestinal bacterial pathogenicity and medicinal cost (Reis et al, 2018). One of such phytogenic feed additives is mucuna seed (Mucuna pruriens var.…”
Section: Introductionmentioning
confidence: 99%
“…Dietary supplementation of meal and protein isolate of Mucuna increased the activity of CAT in organs and plasma of birds, implying that free radical formation could be prevented in broilers by dietary meal and protein isolate supplementation. This observation suggests that dietary meal and protein isolate of Mucuna could contain substances that can act either by stimulating the synthesis of antioxidant enzymes or by preventing their denaturation or their inhibition by free radicals [41].…”
Section: Discussionmentioning
confidence: 98%
“…Although it was reported that animal could ingest sublethal doses of cyanide over an extended period without harm in terms of mortality due to rapid detoxification (Mengel, Kramer, Isert, & Friedberg, 1989), continuous or repeated exposure and subsequent accumulation of cyanide (toxin) in the body fluids, tissues, and organs of the animals for a long period of time (chronic exposure) may predispose the animal to oxidative stress (Lei et al, 2017) and subsequently caused negative effects on biological activities and compromised performance (Halliwell & Gutteridge, 1989;Oloruntola, Ayodele, Adeyeye, & Agbede, 2018) as recorded in this study. Also, the multi-enzyme supplementation's positive significant (P < 0.01; 0.05) influence on the weight changes of the growing rabbits could be due to improvement of nutrient utilization (Boguhn & Rodehutscord, 2010;Lukuyu et al, 2014;Yang et al, 2010) and possible breaking down of anti-nutritive fractions (Bimrew, 2014;Lukuyu et al, 2014) in the diets by enzyme complex in the multi-enzyme used in this study.…”
Section: Discussionmentioning
confidence: 99%